1961
DOI: 10.1111/j.2042-7158.1961.tb11868.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Biochemical Effects of Some Reserpine Derivatives

Abstract: A relation exists between the hypotensive properties of three reserpine derivatives ( /l-diethylaminoethyl reserpine, isobutylserpentinate, 10methoxydeserpidine) and their ability to release cardiac catecholamines. These derivatives do not show sedative properties and do not release 5-hydroxytryptamine or catecholamines from the brain.AT the same time as the discovery of carbethoxy-siringoylmethyl reserpate, a reserpine derivative (Plummer, Barrett, Maxwell, Finocchio, Lucas and Earl, 1959) with specific hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1963
1963
1981
1981

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…This suggests that reserpine inhibits ovulation because it produces changes in the CNS which are not produced by methoserpidine (Garattini, Lamesta, Mortari & Valzelli, 1961;Leroy & De Schaepdryver, 1961). A site of action for reserpine outside the CNS cannot, however, be excluded com¬ pletely because its peripheral effects are not identical with those of methoserpidine.…”
Section: Discussionmentioning
confidence: 95%
“…This suggests that reserpine inhibits ovulation because it produces changes in the CNS which are not produced by methoserpidine (Garattini, Lamesta, Mortari & Valzelli, 1961;Leroy & De Schaepdryver, 1961). A site of action for reserpine outside the CNS cannot, however, be excluded com¬ pletely because its peripheral effects are not identical with those of methoserpidine.…”
Section: Discussionmentioning
confidence: 95%
“…DL-152 has been shown to be a potent inhibitor of cyclic AMP phosphodiesterase (Honda and Imamura 1968) and to induce elevation of cyclic AMP levels in several tissues (Lehnert 1979 a, Honda andImamura 1968) . In the present study both tumours showed the same pattern of cyclic AMP changes following DL-152 administration, maximum levels being seen at 30 min after injection .…”
Section: Discussionmentioning
confidence: 98%
“…However, there are several indications that the use of this drug as an adjunct to radiotherapy is worth investigating . DL-152 is a drug which has already been used clinically and data are available as to its pharmacology in mice (Garattini et al 1961) . DL-152 is particularly effective in protecting the skin against radiation damage, and for both skin and intestine the DMF increases as dose decreases, suggesting that it would be effective in protecting against the effects of a series of small dose fractions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plummer et al (14) and Orlans et al (15) reported that the low doses of syrosin gopine which exhibited no inhibitory effect on conditioned avoidance response caused norepinephrine depletion in the heart and, therefore, syrosingopine appeared to cause a fall in blood pressure by depleting catecholamines in the peripheral tissues. Garattini et al (16) suggested that the fall in blood pressure caused by reserpine and bietaserpine could be correlated with the norepinephrine level in the heart. Furthermore, the central actions of CD-3400 such as a tranquillization, hypothermia or hypnosis and the depletion of serotonin level in the brain were weaker than those of rescinnamine and reserpine (17).…”
Section: Resultsmentioning
confidence: 99%